The Influence Of Financial Literacy And Financial Technology On The Financial Performance Of Msmes: A Study on MSMEs in West Jakarta - Isfandiari M Bahanan; Maman Sulaeman (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to examine the effect of financial literacy and financial technology on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in West Jakarta. A quantitative survey method was applied. The population comprised 38,240 registered MSMEs in West Jakarta. Using the Slovin formula with an 8% margin of error, 150 respondents were selected through proportionate stratified random sampling. Data were collected via a five-point Likert scale questionnaire and analyzed using multiple linear regression with SPSS 26.0. The t-test results show that financial literacy has a positive and significant effect on financial performance (beta = 0.412; t = 6.149; sig. = 0.000), and financial technology also has a positive and significant effect (beta = 0.368; t = 5.183; sig. = 0.000). The F-test yields F = 48.621 (sig. = 0.000), confirming simultaneous significance. The coefficient of determination (R²) is 0.397, indicating that 39.7% of MSME financial performance variation is explained by both variables. This study recommends enhanced financial literacy education and accelerated digital financial technology adoption among MSMEs in West Jakarta